Students' Impressions on the Effectiveness of Online Discussion Forums - Beena Vijayavalsalan (Research in Social Sciences and Technology, 2018)
Purpose: The study has evaluated the effectiveness of online discussion forums among the students of Abu Dhabi University, UAE. Results: The results have shown strong association between positive learning experience and frequency of student participation in discussion forums. However, no statistical significance (p-value=0.306) has been observed among online forums and age of the participants for developing critical thinking skills. Moreover, a significant difference has been identified in students' participation on the effectiveness of online discussion (p-value=0.000). Conclusion: It is concluded that online discussion forums serve as an efficient and effective tool for interaction among the participants.